A hydro-socio-legal conception of rights for water: addressing jurisprudential tensions to foster responsive legal regimes - Wescombe, N (2021)
In the space of ten years, a number of novel and unique legal developments have arisen in different jurisdictions around the world with one element in common: a declaration of the Rights of Nature, and a direct attribution of this jurisprudence to watercourses in their respective contexts. This thesis uses a hydro-socio-legal approach to analysing three of these developments as case-studies, identifying why they have occurred, the tensions involved, and the institutional and governance issues that they seek to address or are responding to. This work frames the analysis around an evaluation of environmental constitutionalism, and legal personhood, which informed their selection. This evaluation is prefaced by a prior discussion of key ideas in the theoretical discourse pertaining to the appropriate form of a right for non-human entities, and whether natural objects can have identifiable, and representable, interests. This work concludes that sufficient sophisticated recognition and processing of information about socio-hydrologies in respective contexts can innovate water law to enable responsive governance regimes, and the achievement of this depends on whether jurisdictions are prepared to open themselves to new approaches, legitimate stakeholder relationships with watercourses, and technological solutions that can enrich empirical understandings of fair resource allocation and utilisation for both nature and society.